Principles of Development and Cultivation of Historical Consciousness in Pregradual Education of Teachers of Civics - Labischová, Denisa; Krákora, Pavel (Civilia, 2019)
This article deals with the problems of historical consciousness in school education in connection with civics and contemporary history. Special attention is paid to questions relating to development and perception of civil society and presentation of given theme in curriculum of civics.
Keywords: Historical consciousness; Civil society; Civics; Contemporary history; Education; Curriculum; Teachers; School; Research